Mixed flow turbine research: a review - Rajoo, Srithar; Martinez-Botas, Ricardo (American Soceity of Mechanical Engineers, 2008)
Research on mixed flow turbines spans over 50 years with substantial literature available in the public domain. Mixed flow turbines were initially used as an alternative rotor design for gas turbines and later extended to automotive turbocharger applications. The characteristics of a mixed flow turbine resemble a radial turbine but with some significant performance improvements, giving this design an edge to satisfy the ever increasing demand in the automotive sector. The initial research focus was mainly experimental but in recent years, there have been significant contributions in computational analysis. This paper is intended to provide readers with a comprehensive review of the past and present research, into the design, performance, and use of mixedflow turbines. Additionally, the future research direction of the mixed flow turbine is discussed in view of the current turbocharger and automotive demand.